Effect of cyanide by sodium nitroprusside (SNP) application on germination, antioxidative system and lipid peroxidation of Senna macranthera seeds under saline stress - Silva,Aparecida Leonir da (2019)
Abstract: The effects of NO donors on germination under saline stress have been much investigated for many species, however, there are reports that the effect caused by donors are effects of cyanide present. The aim of this study was to evaluate the effects of sodium nitroprusside (SNP) on germination, antioxidative system and lipid peroxidation of Senna macranthera seeds under saline stress. The osmotic potentials of -0.4 and -0.5 MPa of NaCl were used, as well as the concentration of 100 μM of sodium nitroprusside, inactive sodium nitroprusside. Germination rate, imbibition curves, antioxidant enzyme activity, lipid peroxidation, and protein content were evaluated. Similar effects were observed for sodium nitroprusside and inactive sodium nitroprusside, indicating that these effects were related to the release of the cyanide present in sodium nitroprusside. The sodium nitroprusside (SNP) improves the germination of Senna macranthera seeds under salt stress conditions, through release of cyanide. The cyanide favored germination, reducing lipid peroxidation and increasing the activity of the antioxidant enzymes.